Dynamic Characteristics of an Experimental MR Fluid Damper - Sapiński, B. (Engineering Transactions, 2003)
The paper provides the results of experimental studies of dynamic characteristics of a linear MRF damper, designed especially for research purposes. Two MR fluids having different viscosity were used in the experiments. Damper design and parameters of the applied MR fluids are discussed. The relationship between the damping force and piston velocity was determined and utilised to identify the involution model of the damper. Currents in the coil were measured for voltage excitations with pulse width modulation and parameters of equivalent model of the control system were identified.